Acute urinary retention due to huge cervical myoma with abdomino-vaginal extensions - Rana, A; Gurung, G; Ojha, N; Anand, B; Amatya, S; Poudel, S; Sharma, S; Mandal, R (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> We happened to manage a case of acute urinary retention that was relieved by drainage of 2L of urine and was sent home to attend out patient Gynecology department next day after the ultrasound diagnosis of huge myoma. This came out to be cervical myoma that filled the vagina pushing the uterus up to the level of the umbilicus. This is in reference to the general interest of everybody that any woman suffering acute urinary retention having gynecological bearing must be well evaluated before disposing them without inserting indwelling catheter. Key words: acute urinary retention in gynaecolgy, cervical myoma Journal of Institute of Medicine, April, 2008; 30:1 65-67 The full text of this paper is available from the Journal of Institute of Medicine website